An Approach to Drug Stability Studies and Shelf-life Determination - Ekta Tembhare; Krishna Radheshyam Gupta; Milind Janrao Umekar (Archives of Current Research International, 2019)
The main objective of carrying out stability studies of the drug product is to establish shelf life of drug during storage. Stability of drug is defined as “The capability of a particular formulation in a specific container/closed system, to remain within its physical, chemical, microbiological, therapeutic, and toxicological specifications throughout its shelf life”. As mentioned in the International Conference on Harmonization (ICH) guideline Q1A (R2), stability studies are commonly the activity on the critical path to regulatory filing and approval. Stability studies are of different types and different methods are useful for the determination of stability like real-time stability testing, accelerated stability testing, retained sample stability testing and cyclic temperature stress testing. pH and temperature are the main factors influencing the stability of the drug. The pH-rate profile (log(k)vs pH) is the pH dependence of the specific rate constant of degradation of compounds. Forced degradation includes deterioration of new drug substances and products at more severe conditions than the accelerated conditions and it indicates the accuracy of stability-indicating methods. The different conditions applied during the forced degradation include hydrolytic, oxidation, photolytic and thermal stress etc. The techniques utilized for evaluation of stability studies can be LC-MS/MS, HPLC-DAD, HPLC-MS, HPLC-UV, HPTLC, TLC, LC-NMR etc. amongst them some techniques shows high sensitivity and resolution power to establish more effective stability-indicating method while for shelf life estimation of drugs and products the different methods mentioned are FDA’s method, the direct method, inverse method, simulation results and Garret and Carper method. Thus stability testing of pharmaceutical products inputs specific scheme in the evolution of a new drug as well as new formulation.